2017
DOI: 10.1590/1980-57642016dn11-040013
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive performance in patients with Mild Cognitive Impairment and Alzheimer's disease with white matter hyperintensities: An exploratory analysis

Abstract: ABSTRACT.Background:White matter hyperintensities (WMH) are commonly associated with vascular dementia and poor executive functioning. Notwithstanding, recent findings have associated WMH with Alzheimer's disease as well as other cognitive functions, but there is no consensus.Objective:This study aimed to verify the relationship between WMH and cognitive performance in Mild Cognitive Impairment (MCI) and Alzheimer's disease (AD) patients. The study also sought to identify cognitive and demographic/cultural fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
(64 reference statements)
2
2
0
Order By: Relevance
“…Associations between WMH and cognitive performance have been widely reported in cognitively normal individuals, 29,30 as well as in individuals with MCI or AD. [31][32][33][34] Our results support the hypothesis that, in older individuals, larger baseline WMH burden is associated with worse cognitive and functional performance as well as accelerated decline in cognition and functional status. We did not find an association between the rate of change in WMH and cognitive and functional trajectory, confirming previous findings 35 and contrasting with others, 36 emphasizing the need to identify new biomarkers sensitive to early and subtle change in WM microstructure.…”
Section: Discussionsupporting
confidence: 83%
“…Associations between WMH and cognitive performance have been widely reported in cognitively normal individuals, 29,30 as well as in individuals with MCI or AD. [31][32][33][34] Our results support the hypothesis that, in older individuals, larger baseline WMH burden is associated with worse cognitive and functional performance as well as accelerated decline in cognition and functional status. We did not find an association between the rate of change in WMH and cognitive and functional trajectory, confirming previous findings 35 and contrasting with others, 36 emphasizing the need to identify new biomarkers sensitive to early and subtle change in WM microstructure.…”
Section: Discussionsupporting
confidence: 83%
“…Our findings showed that PM deficits were associated with both periventricular and deep WMHs in all the participants, while the relationship was not significant when inspecting only the SIVD or AD groups. This finding is partially consistent with the results of Holz et al ( 2017 ), in which a trend of correlation was only found between PM and WMHs in a group of people with MCI and mild AD ( p = 0.052). Therefore, the impact of WMHs on PM may be threshold-sensitive.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, older adults completed a comprehensive neuropsychological assessment battery which evaluated executive functions, attention, language, praxis, and memory. Further information on this assessment battery is available in an article published by Holz et al 52 Only subjects whose cognitive evaluations excluded the presence of cognitive impairment (i.e. z-scores greater than -1.5 on every cognitive domain) were included in the final sample.…”
Section: Methodsmentioning
confidence: 99%